On chaotic behavior of a fixed offshore structure - Cassiano, Jeferson; Balthazar, José Manoel [UNESP] (World Scientific Publ Co Pte Ltd, 2009)
In this paper we analyze the qualitative behavior of a fixed offshore oil platform under sea action perturbation (flows and tides), which is modeled by an inverted rigid pendulum with an elastic articulation at sea surface. We study their bifurcation properties provided by analytical framework and investigate their response to small oscillations, considered a more realistic case taking into consideration the platform features as flexibility and saturation.Our goal is to establish analytic conditions for chaotic oscillations occurrence in this model using the Poincare-Mel'nikov's criterion for separatrix splitting in transverse orbits, considering external periodic force.
Keywords: Nonlinear dynamics; fixed offshore platform; homoclinic chaos; Poincare-Mel'nikov's criterion